Informed consent and group vulnerability in the context of the pandemic (BioLaw Journal - Rivista di BioDiritto, 2021)
Group vulnerability is a standard issue in bioethics. Research ethics guidelines highlight the need for protection of vulnerable participants, and clinical trials are ruled by ethical and legal principles that concern possible health inequities experienced by vulnerable populations. In both the literature and the regulation, two conceptions of vulnerability are at work. On the one hand, the inherent vulnerability that is part of the human condition; on the other hand, the situational vulnerability that is associated with specific contextual factors, and that point out either a reduced autonomy or a greater risk of harms for individuals belonging to some groups. Both these two conceptions of vulnerability are exacerbated during a pandemic; on the one hand, specific populations are at heightened risk for medical complications from the virus (elderly, or immunodepressed); on the other hand, specific groups experience an increased vulnerability due to the social determinants of health, which influence individual resilience and exacerbate the impact of the virus. Among the many (income distribution, education and literacy, working condition, house and living conditions, disability, access to health services, etc.) the dramatic reduction of the space for free and informed consent, because of the mental and physical adverse effects coming from social isolation, age, culture, literacy, is relevant for both clinical research and practice. In this paper, I will discuss challenges for the informed consent in the context of the Covid-19 pandemic, with specific consideration of the condition of vulnerable groups.
Keywords: Covid-19; informed consent; research ethics; vulnerability